Green Infrastructure Financing Institutional Investors, PPPs and Bankable Projects - Koh, Jae Myong (Springer International Publishing, 2018)
This book explores the role of governments and international financial institutions (IFIs) in mitigating the perceived risks in green infrastructure markets of emerging and developing countries. Although green infrastructure is designed to enhance a country's wealth, the author sheds light on the way that the market is failing to link up institutional investors' needs for a stable yield with the demands of potentially financially-viable investments in green infrastructure markets. Providing a detailed analysis of the root cause of this market failure, this innovative book offers powerful solutions for developing countries. An essential read for academics of development economics and international finance, as well as practitioners and policy-makers, this book covers topics such as industrial policy, climate governance, carbon markets and capital markets. .